Ответы и объяснения

  • Эль96
  • почетный грамотей
2014-01-15T18:01:09+00:00
1.  ОДЗ:
1) -2cosx ≥ 0
cosx ≤ 0
x ≤ Pi/2 + Pi*n, n∈Z
2) √(-2cosx) - 1 ≠ 0
-2cosx ≠ 1
cosx ≠ -1/2
x ≠ 2Pi/3 + 2Pi*n, n∈Z
2.  (3^(2sin²x) - 3^(√3sinx)) / (√(-2cosx) - 1) = 0
     3^(2sin²x) - 3^(√3sinx) = 0
      2sin²x - √3sinx = 0
      sinx*(2sinx - √3) = 0
1) sinx = 0
x = Pi*n, n∈Z
2) 2sinx - √3 = 0
sinx = √(3)/2
x = ((-1)^n)*Pi/3 + Pi*n, n∈Z



 sin3x = 4sinx*cos2x
3sinx - 4sin³x = 4sinx*cos²x - 4sinx*sin²x 
3sinx - 4sin³x = 4sinx*cos²x - 4sin³x
3sinx = 4sinxcos²x
4sinx*cos²x - 3sinx = 0
sinx*(4cos²x - 3) = 0
1.  sinx = 0
      x = Pi*n, n∈Z
2.  4cos²x - 3 = 0
     4cos²x = 3
     cos²x = 3/4
1) cosx = (√3)/2
x = ±Pi/6+2*Pi*n, n∈Z
2) cosx = -(√3)/2
x = ±5Pi/6 + 2Pi*n, n∈Z



Ûßö...=)